EKOPASTORAL SEBAGAI RESPONS TERHADAP MASALAH LINGKUNGAN HIDUP DI PAROKI SANTO MAXIMILIANUS KOLBE, WUKIR - Denar, Benediktus; Daven, Mathias; Jewadut, Jean Loustar; Seran, Florensia Imelda; Efrit, Lestiana (Lembaga Penelitian STKIP Widya Yuwana, 2025)
Nowadays humans are increasingly worried about the increasingly serious condition of the earth due to pollution on land, sea and air as well as massive damage to forests, valleys, mountains, rice fields and springs. It is sure that natural conditions have a very dangerous impact on human lives. That is why the ecological crisis and the social crisis are two things that cannot be separated. In the face of the ecological crisis, the Church must provide a prophetic response. Ecopastoralism is one of the Church's responses to ecological problems. This research aims to explain ecopastoralism as a response to environmental problems in the Parish of St. Maximilianus Kolbe, Wukir. The method used in this research is a qualitative method and a case study approach to pastoral programs in the environmental sector and the concrete work of Wukir Parish people in the environmental sector. Data was collected through observation, interviews, and document analysis of various reports. The results of this research show that ecopastoralism in Wukir Parish is carried out with a basic pattern that refers to the duties of the Church, namely liturgy, kerygma, koinonia, and diakonia. The tasks of the Church are always connected with ecology in order to raise awareness among the people about the important role of the natural environment and other creations for human life in the world. Ecopastoralism in the Wukir parish contributes to strengthening the environmental Christian community. This community strives to live out an ecological perspective, develop ecological spirituality as an inner spirit to care for and preserve other creations, and culminates in ecopraxis, namely concrete actions in the environmental sector.